Coil-based high-frequency modeling of permanent magnet synchronous machines with single-tooth windings - Peng, Hujun; Yu, Yue; Stevic, Svetomir; Mönninghoff, Sebastian; Hameyer, Kay (Archives of Electrical Engineering (Online), 2025)
This paper presents a coil-based model for a permanent magnet synchronous machine (PMSM) with single-tooth windings to analyze the voltage distribution along its stator winding. The model encompasses considerations for the skin effect, the proximity effect of the winding, and parasitic capacitance within the machine. The model is parameterized using impedance measurement results. Subsequently, it undergoes validation in both the frequency and time domains. In the frequency domain, validation is carried out by comparing the measured and simulated impedance spectra. In the time domain, voltage and current signals are recorded from an operating machine on the test bench. The modeled and measured voltage and current signals during switching processes of power electronic devices are compared for validation in the time domain.